The Use of Observational Data in Elementary Counselling - Hoge, Robert D. (Canadian Journal of Counselling and Psychotherapy, 2012)
A strategy for dealing with problems of underachievement within the elementary classroom is proposed. The strategy entails collection of behavioral data within the classroom by the consultant and the development of intervention strategies to be implemented by the classroom teacher. It is suggested that current research on the classroom behavior-academic achievement relation can serve as a source of behavioral measuring instruments. The strategy stresses the importance of a cooperative relation between consultant and teacher in the process of interpreting the behavioral data and in the process of arriving at decisions respecting intervention procedures.